Analysis of heart rate variability of female hand-ball athletes after exhaustive exercise - Zhu, X.; Yan, Z.; Liu, L. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Heart rate variability (HRV) is one of the non-invasion electrocardiogram indexes that can be used to evaluate the activity of the autonomic nervous system (ANS). To explore the possibility of the use of HRV in exercise monitoring, the present paper studied the change of the time domain and frequency domain of HRV after exhaustive exercise in 19 female hand-ball athletes. Methods This study explored the changes of the 5min electrocardiogram (ECG) in 19 female hand-ball athletes under rest and post - maximal oxygen uptake exercise. The changes of SDNN, RMSSD, SDSD, TP, LFnorm, HFnorm, LF/HF were analyzed. Results The values of SDNN, RMSSD, SDSD, TP, LF, LFnorm, HF, HFnorm decreased significantly after exhaustive exercise (p<0.01). LF/HF increased significantly after the exercise (p<0.01). The average Maximal Oxygen Uptake in 19 athletes was 39.76±2.34 (ml/kg.min), the average maximal heart rate was 180±9 (b/min). Discussion / Conclusions HRV reflects the time difference of every cardiac cycle and is regulated by the ANS. By analyzing the time domain and frequency domain, it was found that the tendency of transient fluctuation decreased after exhaustive exercise in 19 athletes. LF/HF ratio was significantly higher after exhaustive exercise (p<0.01). This suggested the disequilibrium between sympathetic nerve activity and vagus nerve activity. Both the sympathetic nerve and vagus nerve tone levels decreased, but the decrease of vagus nerve tone level was considerably more. The female hand-ball athletes at rest were characterized by stronger sympathetic nerve activity and lower vagus nerve activity. This demonstrated the adaptability of ANS to long-term exercise. This non-invasive method was an excellent tool to evaluate exercise adaptation. HRV was a significant index for exercise monitoring.